EKOFEMINISME QURANI PERSPEKTIF AL-QUR’AN TERHADAP RELASI PEREMPUAN DAN ALAM DALAM NARASI EKOLOGIS - Imron Taslim (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
The ecological crisis and gender inequality are two interrelated global issues rooted in patriarchal and exploitative social structures. In this context, ecofeminism offers a critical perspective on the dual domination of nature and women. This study aims to explore how the Qur’an constructs the relationship between women and nature through a thematic interpretation (tafsīr maudhū‘ī) combined with the framework of Qur’anic ecofeminism. This research employs a qualitative method based on library research, using critical hermeneutics to analyze selected verses of the Qur’an, such as QS. An-Nahl [16]: 97, QS. Ar-Rum [30]: 41, QS. Maryam [19]: 23–26, and QS. Az-Zalzalah [99]: 2. The findings reveal that the Qur’an does not only offer separate spiritual values to women and nature but also constructs a symbolic and functional relationship between them. The Qur’anic narratives of female figures, such as Maryam and the Queen of Sheba, demonstrate ecological agency rooted in ethics and spirituality. Simultaneously, nature in the Qur’an is portrayed as a responsive, sacred entity that reacts to human behavior. This study concludes that the Qur’anic ecofeminist perspective contributes to a new ethical and theological paradigm in Islamic interpretation—one that promotes ecological awareness, gender justice, and collective responsibility for caring for the Earth.